Assessing the Impact of LED Lighting on the Stability of Selected Yellow Paint Formulations. Issue 1 (2nd January 2020) - Richardson, Emma; Woolley, Elizabeth; Yurchenko, Asya; Thickett, David
ABSTRACT: Light emitting diodes (LEDs) are steadily finding application in an increasing number of museums and heritage institutions, providing energy-efficient solutions for collections display. Although there is a business case to be made for moving toward LED lighting, the safe display of objects must also be ensured. Identifying vulnerable pigments and paints ensures that future preservation strategies will be put in place, avoiding acerbation of damage and reducing the need for conservation. In the first part of our research we investigate color shift and molecular alterations in three yellow paints, namely, lead chromate sulfate, arsenic sulfide, and cadmium sulfide in linseed oil and gum arabic binders. Following an artificial aging regime, color shift was evaluated using colorimetry and molecular alterations were monitored using attenuated total reflectance–Fourier transform infrared spectroscopy coupled with multivariate analysis. Up to 80 Mlux h the lead chromate samples in linseed oil displayed equivalent color shifts approximating 10 ∆ E 00 on exposure to the three artificial aging regimes. Color shift has been attributed to the formation of lead oxides evidenced by the appearance of a mid-infrared spectral band at 470 cm −1 assigned to PbO2 . Above 80 Mlux h the formation of lead oxides was exacerbated by exposure to one particular LED. Arsenic sulfide in linseed oil displayed color shifts intensified by both types of LED. Above 40 Mlux h there was a discernible color shift in all samples, with the two LEDs displaying ∆ E 00 values two times higher than those displayed by the tungsten halogen samples. The alterations have been attributed to the formation of As2 O3, which is known to form in the presence of wavelengths shorter than 428 nm. Cadmium sulfides in both linseed oil and gum arabic paints did not display discernible color shifts or the presence of degradation products.